A competitor’s reflections : reflections about competing in an international architectural competition: LE:NOTRE Student Competition - (re)discovering the emerald necklace of Colentina - Wedlin, Arvid (SLU/Dept. of Urban and Rural Development, 2015)
In the profession of architects there is an element called architectural competitions, where several architects compete in submitting the best solution for a certain task. In this master’s thesis I am studying the competitor’s perspective of an international architectural competition, while at the same time gaining experiences for my future career as a landscape architect. The aim of this thesis is to through an introspection of my own process examine a competitors view of the international architectural competition and how to approach the difficulties concerning international competitions. Through that I hope obtain experience about the international competition as part of the profession of landscape architects and other involved professions. To examine a competitor’s reflection of an international competition, I entered and competed in LE:NOTRE Student Competition, a competition for students where the task was to develop 25 kilometers of complex urban periphery along a chain of natural and artificial lakes in Bucharest, Romania. My working process contained a five step method of Research - Conceptual ideas - Inventory - Analysis - Proposal where I went from knowing nothing at all about the site and the task, to completing a proposal and submitting it in the competition. The idea of my competition submission called Retain, Restore and Revive, build upon the intentional purpose of the artificial lakes; to serve as water supply, irrigation, fishing and primary leisure. Existing values will be retained, vacant lands and available shores will be restored into green spaces and the entire area will be revived with a new identity uniting people and attracting tourists. Discussing the working process and the results, I bring up the difficulties in competing in an international architectural competition and what experiences I obtained through my introspection of my participation in a competition. I also discuss creating a competition submission that is both innovative and unique and at the same time fulfills the aim and requirements. Furthermore, I discuss the wider perspective of international architectural competitions, if they contribute in creating high quality architecture or not and if they may contribute in a global generalization of architecture and less cultural differences in the long term. Lastly, I mention my own experience and development when completing this competition and the master’s thesis, how I have found myself as a landscape architect and the harmony in designing.